EFFECTIVE TRAINING: SYSTEMS STRATEGIES AND PRACTICES - Blanchard Nick; Thacker James W (Pearson, 2004)
OVERVIEW OF TRAINING IN ORGANIZATIONS STRATEGIC PLANNING, TRAINING AND OD LEARNING MOTIVATION AND PERFORMANCE NEEDS ANALYSIS TRAINING METHODS DEVELOMPENT AND IMPLEMENTATION OF TRAINING
OVERVIEW OF TRAINING IN ORGANIZATIONS STRATEGIC PLANNING, TRAINING AND OD LEARNING MOTIVATION AND PERFORMANCE NEEDS ANALYSIS TRAINING METHODS DEVELOMPENT AND IMPLEMENTATION OF TRAINING